1998
DOI: 10.1001/archotol.124.11.1251
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Diagnosis of Oral Neoplasia Based on Fluorescence Spectroscopy and Native Tissue Autofluorescence

Abstract: Consistent differences exist between the fluorescence spectra of abnormal and normal oral mucosa. Therefore, fluorescence spectroscopy has the potential to improve the noninvasive diagnosis of oral cavity neoplasia. Further studies will better define the role of this technique in the detection of premalignant and early oral cancer lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
152
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(165 citation statements)
references
References 15 publications
7
152
0
1
Order By: Relevance
“…Several studies have demonstrated that fluorescence spectroscopy can be used for discrimination of normal and malignant oral tissues. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] We have developed a Raman spectroscopy method with specificity and sensitivity better than 95%, for discrimination of normal and malignant tissues in oral cancers. 20,21 Recent Raman microspectroscopy studies of formalin-fixed oral tissues have validated the use of these samples in optical pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that fluorescence spectroscopy can be used for discrimination of normal and malignant oral tissues. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] We have developed a Raman spectroscopy method with specificity and sensitivity better than 95%, for discrimination of normal and malignant tissues in oral cancers. 20,21 Recent Raman microspectroscopy studies of formalin-fixed oral tissues have validated the use of these samples in optical pathology.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, both practitioners and patients are often reluctant to perform the invasive, sometimes painful biopsies that are required to confirm the presence of precancer or even early cancer. 8 Thus, despite the easy accessibility of the oral cavity to examination, there is no satisfactory method to adequately screen and detect precancers noninvasively. Developing noninvasive and accurate techniques that can facilitate the early detection of neoplastic changes has great potential to improve survival rates and lower treatment costs in persons prone to have malignancies develop in the oral cavity.…”
mentioning
confidence: 99%
“…The selection of the excitation and observation filter combinations was governed by previous analyses performed in our laboratory. In two spectroscopic studies, 8,19 we measured the intensity of fluorescence of normal and neoplastic oral sites as a function of excitation and emission wavelength. In this work, we demonstrated that quantitative measurement of tissue fluorescence intensity could yield greater sensitivity and specificity relative to clinical examination, with best results at 350-, 380-, and 400-nm excitation.…”
mentioning
confidence: 99%
“…For instance, direct fluorescence visualization has been used in different tissues and organs and successfully distinguished premalignant and malignant lesions that cannot be detected by naked eye [22][23][24][25][26]. In our study, spectroscopy satisfactorily discriminated normal tissue and slightly altered mucosa from cancerous lesions.…”
Section: Discussionmentioning
confidence: 55%